Application of The Lampit MSME Canvas Model in Wetland Areas, North Hulu Sungai Regency - Humaidi Humaidi; Setio Utomo; Isty Juraiha; Ria Rizqi Norwidyanti; Wildan Rizqi (Cita Konsultindo Research Center, 2022)
The purpose of this research activity is to create a Business Model Canvas and describe the SWOT of the Lampit SMEs in Wetland Areas. The model produced in this study is expected to be able to contribute to increasing the Small and Medium Enterprises of Lampit in Wetland Areas, North Hulu Sungai Regency. The specific objectives of this research are a) Creating a Business Model Canvas Small Medium Enterprises in Wetland Areas of North Hulu Sungai Regency, b) Describing SWOT of the Business Model Canvas of Small SMEs in Wetlands of North Hulu Sungai Regency. The research method uses a qualitative approach which is essentially observing people in their environment, interacting with them, trying to understand their language and interpretation of the world around them. This study uses a descriptive type of research, namely research conducted to determine the value of independent variables, either one or more variables (Independent) without making comparisons, or connecting with other variables. Therefore, the researcher will provide the results of this study to describe/construct in-depth interviews with research subjects so that they can provide a clear picture of the application of the Lampit MSME Business Canvas Model in Wetland Areas, Hulu Sungai Utara Regency. The results show that the MSMEs of Lampit Products have indirectly implemented the concept of a business model canvas in carrying out their business, which is indicated by the presence of nine blocks. In addition, MSMEs for Lampit products are obtained SWOT analysis using the SWOT Matrix to obtain strategies that can help survive and develop MSMEs for Lampit Products. Keywords: Business Model Canvas, SWOT Analysis, UMKM Lampit